Pengembangan Kreativitas Anak Melalui Kurikulum Plus - Yasmin Faradiba; Yudrik Jahja; Awaliyatun Khasanah (Jurnal Pendidikan Indonesia, 2022)
The early age range is an important period for children to develop their creativity. Not only that, the environment is also one of the factors that can affect children's creative thinking abilities to be optimal. Creativity is very necessary in the development of children because it will affect the work of the right brain and left brain. So if a child's creativity develops well, then the child will experience the development of an independent, confident, and productive personality. On the other hand, if children's creativity does not develop well, they will experience personality growth that is still dependent, less confident, easily discouraged, and unproductive. Creativity is very necessary for early childhood, especially children aged 5-6 years, because with children growing creatively they will be able to produce innovative works or something new that is needed by the times. The growth of children's creativity can be stimulated through the curriculum of learning activities in schools. In this study, the authors developed several activity programs to hone children's creativity through the learning curriculum at school. The research method that the author uses is the ADDIE method. As for this study, only 3 of the 5 steps of development in the ADDIE model are used, namely analysis, design, and development due to adjusting the current conditions in the field. The results of the study are in the form of several learning activity programs including the "Green Camping" class program, "Kreasi Knitting" class and "Entrepreneurial" class. This program is designed to be able to hone children's creativity in everyday life as the times are increasingly sophisticated.